Early detection of neuropathy in patients with type 2 diabetes with or without microalbuminuria in the absence of peripheral neuropathy and retinopathy - YAVUZ, DİLEK; GÜNDÜZ, OSMAN HAKAN (MASSON EDITEUR, 2021)
Purpose. - Our goal is early detection of neuropathy in patients with type 2 diabetes with or without microalbuminuria in the absence of diabetic retinopathy and peripheral neuropathy by using in vivo corneal confocal microscopy (IVCCM). Methods. - A total of 60 type-2 diabetic patients, assigned to either a diabetes mellitus (DM) with microalbuminuria group (DM/MA+, n = 30) or a DM without microalbuminuria group (DM/MA-, n = 30), and 30 age-matched control subjects were enrolled in this study. All cases underwent evaluation of blood glucose level, HbA(1c), lipid fractions, body mass index (BMI), and corneal sensitivity (CS). Corneal nerve fiber length (NFL), nerve fiber density (NFD), nerve branch density (NBD), and tortuosity coefficient (TC) were quantified by IVCCM. None of the patients had peripheral neuropathy or retinopathy. Results. - Compared with the healthy subjects, NFL and NFD were reduced in both diabetic groups (P < 0.0001), while NBD was significantly reduced in the DM/MA+ group. Between the diabetic groups, NFL, NFD, and NBD were significantly higher in the DM/MA-group (all P's < 0.001). CS was significantly lower in DM/MA+ compared with DM/MA- and controls (both P's < 0.0001). NFD and NFL were inversely correlated with age, triglyceride level, and BMI. Conclusion. - These results indicate that significant damage to small nerves, quantified using IVCCM, can be detected in the absence of retinopathy, peripheral neuropathy or microalbuminuria in type 2 diabetic patients. The severity of corneal nerve involvement may further increase in the presence of nephropathy. This feature may also be valuable for early detection of microvascular complications of DM, allowing for the prevention of progression of life threatening microvascular complications. (C) 2021 Elsevier Masson SAS. All rights reserved.
Keywords: Confocal microscopy; Cornea; Diabetic neuropathy; IVCCM; Microalbuminuria; CORNEAL CONFOCAL MICROSCOPY; RISK-FACTORS; LONGITUDINAL ASSESSMENT; HEART-FAILURE; POLYNEUROPATHY; MORPHOLOGY; MORTALITY; SEVERITY; DESIGN